Effects of short-term exposure to particulate matter on emergency department admission and hospitalization for asthma exacerbations in Brescia district. (13th June 2022) - Pini, Laura; Giordani, Jordan; Concoreggi, Carlo; Zanardini, Elena; Pini, Alessandro; Perger, Elisa; Bargagli, Elena; Di Bona, Danilo; Ciarfaglia, Manuela; Tantucci, Claudio
Abstract: Background: Rising pollution plays a crucial role in worsening several respiratory diseases. Particulate Matter (PM)-induced asthma exacerbations are one of the most dangerous events. Objectives: To assess the correlation between progressive particulate matter short-term exposure and asthma exacerbations, we investigated the role of PM levels on Emergency Department (ED) admissions and hospitalizations for these events in Brescia, an important industrial city located in northern Italy with high yearly levels of air pollution. Methods: We analyzed 1050 clinical records of ED admissions for suspected asthma exacerbation, starting from January 2014 to December 2017. Daily PM levels were collected from the Environmental Protection Regional Agency. We performed a time-series analysis using a Poisson regression model with single and multiple day-lag. Results were expressed as Relative Risk (RR) and Excess of Relative Risk (ERR) of severe asthma exacerbation over a 10 µg/m 3 increase in PM10 and PM2.5 concentration. Results: We selected and focused our analysis on 543 admissions for indisputable asthma exacerbation in ED and hospital. The time-series study showed an increase of the RR (CI95%) for asthma exacerbation-related ED admissions of 1.24 with an ERR of 24.2% for PM2.5 at lag0–1 ( p < 0.05). We also estimated for PM2.5 a RR (CI95%) of 1.12 with an ERR of 12.5% at lag0–5 ( p ≤ 0.05). Again, for PM2.5, an increase of the RR (CI95%) for asthma exacerbation-related hospitalizations of 1.31 with an ERR of 30.7% at lag0–1 ( p < 0.05) has been documented. These findings were confirmed and even reinforced considering only the population living in the city. Conclusions: Short-term PM exposure, especially for PM2.5, plays a critical role in inducing asthma exacerbation events leading to ED admission or hospitalization.